Distance-mediated plasmonic dimers for reusable colorimetric switches : a measurable peak shift of more than 60 nm - Li, Chang Ming (2014)
The first reconfigurable colorimetric DNA switches based on target DNA binding are reported. This DNA binding actuates a change in the interparticle distance between gold nanoparticle dimers. A significant spectral shift of 68 nm is achievable from on-off switching. The reconfigurability is possible owing to thiol and EDC-imidazole coupling which anchors the DNA linkers to the nanoparticles. The huge spectral shift allows the unaided eye to observe single target biomolecular binding event in real time under a darkfield microscope. The limit-of-detection for target molecules in PBS and human serum are 10−13 M and 10−11 M respectively. An improved fabrication strategy via asymmetric functionalization is also described, assisted by solid phase synthesis which minimizes the formation of trimers and multimers.